2005
DOI: 10.1093/hmg/ddi178
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific gene expression of midbrain dopaminergic neurons reveals molecules involved in their vulnerability and protection

Abstract: Molecular differences between dopamine (DA) neurons may explain why the mesostriatal DA neurons in the A9 region preferentially degenerate in Parkinson's disease (PD) and toxic models, whereas the adjacent A10 region mesolimbic and mesocortical DA neurons are relatively spared. To characterize innate physiological differences between A9 and A10 DA neurons, we determined gene expression profiles in these neurons in the adult mouse by laser capture microdissection, microarray analysis and real-time PCR. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
347
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 350 publications
(387 citation statements)
references
References 89 publications
32
347
1
2
Order By: Relevance
“…Consistent with this possibility is the fact that mature DA phenotypic traits, such as the expression of the key DA rate-limiting enzyme TH or the second enzyme in DA biosynthesis AADC, were never observed at either the transcriptional or protein levels in these cells. Nonetheless, the DA-associated Girk2 channel [21][22][23] was detected by RT-PCR both in this study and by Atala and colleagues who also demonstrated its functionality (i.e., barium sensitivity) in culture [17]. As Girk2 expression has also been reported in a variety of non-DA neurons [24][25][26], proof that its expression here represents the acquisition of a bona fi de DA neuronal trait will require experimental corroboration by other methods.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with this possibility is the fact that mature DA phenotypic traits, such as the expression of the key DA rate-limiting enzyme TH or the second enzyme in DA biosynthesis AADC, were never observed at either the transcriptional or protein levels in these cells. Nonetheless, the DA-associated Girk2 channel [21][22][23] was detected by RT-PCR both in this study and by Atala and colleagues who also demonstrated its functionality (i.e., barium sensitivity) in culture [17]. As Girk2 expression has also been reported in a variety of non-DA neurons [24][25][26], proof that its expression here represents the acquisition of a bona fi de DA neuronal trait will require experimental corroboration by other methods.…”
Section: Discussionsupporting
confidence: 65%
“…Chung et al identified 52 genes that were expressed at higher levels in SN neurons than VTA neurons (36). Of these, 19 were down-regulated in 10-wk Tfr1-CKO mice compared with controls: Anxa1, Aldh1a7, Sncg, Atp2a3, Srpx2, Tyrp1, Rerg, Grin2c, Cd24a, Trhr, Sox6, Pvrl3, Lix1, Satb1, Igf1, Nrip3, Sox6, Vav3, and Fgf1.…”
Section: Resultsmentioning
confidence: 99%
“…Coexpression of TH and G-protein coupled inward rectifying current potassium channel type 2 (Girk-2) defines the most vulnerable population of DA neurons in PD [7,33]. This group of DA neurons is located in the ventral tier of adult SN pars compacta (A9 SNc), projecting axons and terminals to motor areas of the putamen.…”
Section: Organotypic Distribution Of Grafted Fetal Da and Non-da Neuronsmentioning
confidence: 99%